753. Performance Characteristics of Diagnostic Assays in Blastomycosis. (31st December 2020) - O'Dowd, Timothy; McHugh, Jack; Wengenack, Nancy; Theel, Elitza; Vergidis, Paschalis
Abstract: Background: Blastomycosis has historically been a difficult diagnosis to establish, often initially misdiagnosed as bacterial pneumonia. Serologic assays and polymerase chain reaction (PCR) tests are available, but their performance is not well defined. The objective of this study was to characterize their performance. Methods: Subjects were identified via chart review of patients diagnosed with blastomycosis from 2005 to 2020. A definitive diagnosis was based on fungal culture, histopathology, or cytology. Performance characteristics of the Blastomyces antibody enzyme linked immunosorbent assay (ELISA), immunodiffusion (ID), complement fixation (CF), urine and serum antigen ELISAs, and PCR were evaluated in patients with confirmed blastomycosis. Data on patient demographics, location of disease, and mortality was also collected. Results: We identified 193 patients with blastomycosis. The mean age was 51.8 years (range, 11-84) and 73.6% of patients were male. 42.5% resided in Minnesota, 18.1% in Wisconsin, and 12.9% in Iowa. Diagnosis was based on culture in 142 (73.2%) or histopathology/cytology in 67 (34.7%) patients. Granulomatous inflammation was present in 73.1% (38/52) while 21.2% (41/193) had evidence of extrapulmonary dissemination. The antibody, ID, and CF assays were positive in 43.5% (37/85), 35.1% (33/94) and 20.5% (8/39) of patients, respectively. Sensitivity of Blastomyces PCR was 40% (4/10) in sputum and 75% (21/28) in bronchoalveolar lavage (BAL) fluid. Blastomyces urine and serum antigen tests were positive in 68% (34/50) and 50% (9/18) of cases, respectively, while the urine antigen was positive in 63.6% (7/11) of disseminated cases. Patients had a positive Histoplasma urine antigen test in 54.1% (20/37) and Aspergillus galactomannan in BAL in 34.8% (8/23) of cases. Serum beta-D-glucan test was positive in 16.7% (2/12). 90-day mortality was 21/193 (10.9%) and median time from diagnosis to death was 18 days. Conclusion: In this cohort, Blastomyces urine antigen was the most sensitive noninvasive test, with similar performance in pulmonary and disseminated disease. However, its utility is limited by poor specificity due to cross-reactivity. Blastomyces PCR from BAL fluid demonstrated the highest sensitivity. Blastomyces antibody, ID, and CF had poor sensitivity. Disclosures: All Authors : No reported disclosures